Media as the Battleground for Politics: The Relation Between Politicians and Media Barons in Indonesian Politics - Fahd Pahdepie (International Journal of Nusantara Islam, 2014)
Media, especially television channels and newspapers have become another political battleground in Indonesian democracy. Some following scenes would describe how Indonesian media empires link to the political system. Media becomes the battleground for politics and there are two point-of-views that could be taken. First, from the perspective of politicians, media is a medium to legitimate their political authority. Second, from the perspective of media barons, politics is an arena that can benefit their business empires. At this point, the marriage between political power and media ownership will eliminate the independence; consequently, the role of media in the concept of democracy to control the power will be diminished or even disappeared.